2017
DOI: 10.1038/s41598-017-02645-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of uterine cervix with a Mueller polarimetric colposcope

Abstract: Mueller polarimetric imaging enables the detection and quantification of modifications of the collagen fibers in the uterine cervix due to the development of a precancerous lesion. This information is not accessible through the use of the classic colposcope, a low magnification microscope used in current practice for cervical cancer screening. However, the in vivo application of Mueller polarimetric imaging poses an instrumental challenge: the device should be sufficiently compact, while still being able to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 44 publications
1
60
0
1
Order By: Relevance
“…Relevant research has demonstrated the ability of Mueller matrix polarimetry to identify colorectal and cervical cancer. [26][27][28] We have developed a preterm imaging system (PRIM) based on a standard colposcope, with a high sensitivity to cervical ultrastructure (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research has demonstrated the ability of Mueller matrix polarimetry to identify colorectal and cervical cancer. [26][27][28] We have developed a preterm imaging system (PRIM) based on a standard colposcope, with a high sensitivity to cervical ultrastructure (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Various imaging techniques, primarily based on transmission, absorption, reflection, spontaneous emission and scattering in light‐tissue interactions, have shown to be responsive to a number of subtle alterations in various diseased tissue. Mueller matrix (MM) polarimetric imaging based on the acquisition of 16 images has shown tremendous potential in precancer detection since the last decade and is best suited for a complete characterization of the biological specimen . These MM images are further processed to extract the essential optical parameters, namely, diattenuation, retardation and depolarization through Lu‐Chipman decomposition method .…”
Section: Introductionmentioning
confidence: 99%
“…31 Polarized images o®er tremendous potential for biomedical applications, which distinguish between healthy and pathological regions 32 on several types of tissues, such as skin, 33 intestine, 34 colon, 35 rectum 36 and cervix. 31,[37][38][39] Li et al studied the use of a digital colposcope, which acquires polarized and nonpolarized color cervical images during a clinical exam. 37 Several image processing algorithms are used to locate the acetovhite lesion.…”
Section: Introductionmentioning
confidence: 99%